2018
DOI: 10.2147/oaem.s171250
|View full text |Cite
|
Sign up to set email alerts
|

Differences in implementation strategies of the European Resuscitation Council Guidelines 2015 in Danish hospitals – a nationwide study

Abstract: IntroductionGuideline implementation is essential to improve survival following cardiac arrest. This study aimed to investigate awareness, expected time frame, and strategy for implementation of the European Resuscitation Council (ERC) Guidelines 2015 in Danish hospitals.MethodsAll public, somatic hospitals with a cardiac arrest team in Denmark were included. A questionnaire was sent to hospital resuscitation committees one week after guideline publication. The questionnaire included questions on awareness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…4,14 In Denmark, previous studies reported on differences in resuscitation teams and guideline implementation strategies across hospitals. [16][17][18] Resuscitation teams at hospitals with high IHCA survival have been shown to differ in features (e.g., team design, communication, and training)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,14 In Denmark, previous studies reported on differences in resuscitation teams and guideline implementation strategies across hospitals. [16][17][18] Resuscitation teams at hospitals with high IHCA survival have been shown to differ in features (e.g., team design, communication, and training)…”
Section: Discussionmentioning
confidence: 99%
“…3,7,10,14,15 However, it remains unclear to what extent patient characteristics may explain potential variations in outcomes. Additionally, while hospital-level variation in resuscitation care strategies has been identified in Denmark, [16][17][18] variation in outcomes remain to be explored.…”
mentioning
confidence: 99%